1987
DOI: 10.1144/gsjgs.144.6.0871
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of the West Orkney Basin, northern Scotland

Abstract: The West Orkney Basin developed in Devonian times, as the western part of the Orcadian intermontane basin. It has been studied using commercial speculative seismic reflection data and the MOIST deep seismic data. The NW edge of the West Orkney Basin is formed by listric faults which are also strongly arcuate in plan, while the SE part is composed of straight domino-type faults which formed parallel to earlier (Caledonian) layering in the basement. Fault restoration and balancing suggest that initial extension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(39 citation statements)
references
References 32 publications
2
36
0
1
Order By: Relevance
“…The timing of the Shetland magmatism has been noted as an outlier (Stephenson 2000), suggesting that Shetland occupied a separate terrane from what is now mainland Scotland. However, more or less contemporaneous magmatism in Shetland and Glen Gollaidh suggests that these regions were not significantly geographically distinct, a conclusion supported by the contiguous pattern of sedimentation in the Orcadian Basin (Enfield and Coward 1987).…”
Section: Mantle Lithosphere Compositionmentioning
confidence: 95%
“…The timing of the Shetland magmatism has been noted as an outlier (Stephenson 2000), suggesting that Shetland occupied a separate terrane from what is now mainland Scotland. However, more or less contemporaneous magmatism in Shetland and Glen Gollaidh suggests that these regions were not significantly geographically distinct, a conclusion supported by the contiguous pattern of sedimentation in the Orcadian Basin (Enfield and Coward 1987).…”
Section: Mantle Lithosphere Compositionmentioning
confidence: 95%
“…The Old Red Sandstone succession of Caithness and Orkney was deposited in a system of westerly-tilted half-graben structurally continuous with those seen on seismic sections in the offshore West Orkney Basin (Enfield & Coward, 1987). In the Moray Firth region, the pattern of sedimentation was controlled similarly by an extensional half-graben system (Rogers, 1987).…”
Section: Geological Settingmentioning
confidence: 99%
“…Watson 1985), he realized that many of the basin structures around the British Isles owed their trends to earlier structures. Thus Enfield & Coward (1987) showed that the West Orkney basin preferentially reactivated the Caledonian deformation fabric, as imaged in the MOIST deep seismic data (e.g. Brewer & Smythe 1984).…”
Section: Basin Evolutionmentioning
confidence: 85%